KEADILAN DAN KESETARAAN GENDER UNTUK PARA PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT) - Dudi Badruzaman (Tahkim (Jurnal Peradaban dan Hukum Islam), 2020)
Forms of violence against women still occur in many places where women are always associated as marginalized groups that are discriminated against, oppressed, and subordinated to male domination. This study aims to 1). Why domestic violence still often occurs in many places in Indonesia even though legislation has been made to protect women's rights. 2). With the analysis of these questions, what should be done in order to reduce violence and provide justice for women in Indonesia. The method used by data collection techniques with literature study methods. And then collected from the reports of relevant agencies such as the National Commission on Violence Against Women, and scientific books that conduct similar studies, these secondary data are then interpreted qualitatively and supported by several scientific concepts and theories that have been put forward previously as a knife of analysis. This paper is expected to be able to raise awareness of the issue of violence against women in academic studies and provide an analysis and analysis of this issue.Keywords: Justice; gender equality; women.